Aggressive Systemic Mastocytosis in Association with Pure Red Cell Aplasia - Dhauna Karam; Sean Swiatkowski; Mamata Ravipati; Bharat Agrawal (Case Reports in Hematology)
Aggressive systemic mastocytosis (ASM) is characterized by mast cell accumulation in systemic organs. Though ASM may be associated with other hematological disorders, the association with pure red cell aplasia (PRCA) is rare and has not been reported. Pure red cell aplasia (PRCA) is a syndrome, characterized by normochromic normocytic anemia, reticulocytopenia, and severe erythroid hypoplasia. The myeloid and megakaryocytic cell lines usually remain normal. Here, we report an unusual case of ASM, presenting in association with PRCA and the management challenges.